Drug-related problems in patients admitted for SARS-CoV-2 infection during the COVID-19 pandemic - Barceló-Vidal, J.; Echeverría-Esnal, D.; Carballo, N.; De Antonio-Cuscó, M.; Fernández-Sala, X.; Navarrete-Rouco, M. E.; Colominas-González, E.; Luque, S.; Fuster-Esteva, M.; Domingo, L.; Sala, M.; Duran, X.; et al. (Frontiers in Pharmacology, 2022)
IINTRODUCTION Drug-related problems (DRP) are events or circumstances in which drug therapy does or could interfere with desired health outcomes. In December 2019, a new coronavirus, SARS-CoV-2, appeared. Little knowledge about this type of infection resulted in the administration of various drugs with limited use in other pathologies. Evidence about DRP in patients with COVID-19 is lacking. OBJECTIVE The aim of the present study is to describe identified cases of DRP and those drugs involved in the first wave of patients with COVID-19, and evaluate associated risk factors. MATERIAL AND METHODS Observational, retrospective study performed in a tertiary university hospital between March 14th and May 31st, 2020 (corresponding to the first COVID-19 wave). We recruited patients admitted during the study period. Exclusion criteria included age <18 years; admission to critically ill units; and care received either in the emergency room, at-home hospitalization or a healthcare center. RESULTS A total of 817 patients were included. The mean age was 62.5 years (SD 16.4)(range 18-97), and 453 (55.4%) were male. A total of 516 DRP were detected. Among the patients, 271 (33.2%) presented at least one DRP. The mean DRP per patient with an identified case was 1.9. The prevailing DRPs among those observed were: incorrect dosage (over or underdosage) in 145 patients (28.2%); wrong drug combination in 131 (25.5%); prescriptions not in adherence to the then COVID-19 treatment protocol in 73 (14.1%); prescription errors due to the wrong use of the computerized physician order entry in 47 (9.2%); and incorrect dosage due to renal function in 36 (7%). The logistic regression analysis showed that patients who received only prescriptions of antibacterials for systemic use (J01 ATC group) faced a higher likelihood of experiencing a DRP (OR 2.408 (1.071-5.411), p=0.033). CONCLUSIONS We identified several factors associated with an increased risk of DRPs, similar to those reported in other pre-pandemic studies, including a prolonged length of stay, higher number of prescribed drugs and antimicrobial administration. The relevance of pharmacists and tools like pharmacy warning systems can help prevent, identify and resolve DRP efficiently.